Car park adviser web application - Ng, Werner Wen Jie (Nanyang Technological University, 2022)
As the urban environment in Singapore increases in density over the years, motorists now face the challenge of vehicle navigation. One aspect of navigation is finding suitable car parks. To address this challenge, users would need access to information about the car parks surrounding their destination to make the most informed decision. Key criteria include the number of available lots, cost of parking at a car park, and car park ergonomics. This project aims to provide a web application, Carparkly, for users to conveniently find and navigate to car parks around their destination. Based on the user’s preferences and input, the web application will provide a list of recommended car parks, which includes additional information such as cost of parking, number of available lots, and distance from destination. It also possesses a community feature that allows users to provide anecdotal reviews and insights into specific car parks. This will allow users to make better decisions regarding parking at their next destination. A considerable amount of solutioning was utilized to optimize the user experience and provide quality information. The web application has a front-end and back-end component. The front end component is developed using the ReactJS library and framework. The back-end component is developed using the Flask Python micro web framework. Data for the web application is gathered via publicly available APIs and through web scraping of government websites. The project is deployed and maintained using Amazon Web Services (AWS) to provision and configure resources. This allows for the development of a web application that is reliable, maintainable, and available to users. This report provides details behind the problem and an in-depth explanation of the project’s implementation and evaluation of results.